Systematic review protocol: The effects of theory-based interventions for self-help practices in the management of mild to moderate depression - Asma’ Khalil; Zahir Izuan Azhar; Norley Shuib; Philip Baker; Xin Wee Chen (PLoS ONE, 2025)
Background This protocol outlines a planned systematic review to assess the effects of theory-based interventions for self-help practices in managing mild to moderate depression. Depression is a leading global cause of disability and contributes significantly to the worldwide burden. Self-help practices present promising avenues for care. When grounded in psychological theory, these interventions may offer a structured and effective approach to symptom management. However, their effectiveness varies and often lack a theoretical foundation. The summarized evidence on theory-based interventions remains limited. Objectives This review aims to evaluate the effects of theory-based self-help interventions in reducing the severity of depressive symptoms among adults with mild or moderate depression. It also aims to report any adverse effects associated with the use of these interventions. Methods The review will follow PRISMA guidelines and is registered with the International Prospective Register of Systematic Reviews (PROSPERO), registration ID: CRD42024613188. Randomized controlled trials published between January 2014 and 2025 will be included in the analysis. Eligible theory-based interventions include Cognitive Behavioral Therapy (CBT), Acceptance and Commitment Therapy (ACT), and Mindfulness-Based Interventions (MBIs), delivered via digital platforms. Studies will be identified through searches of PubMed, Scopus, Web of Science, Science Direct, and Cochrane bibliographic databases. Title and abstract screening will be completed within two months of the initial search, followed by one month for data extraction and two months for synthesis and analysis. Two reviewers will conduct screening, data extraction, and risk of bias assessment independently using the Cochrane Risk of Bias Tool (RoB 2). Key outcomes include changes in depressive symptom severity and adverse effects. Anticipated results The planned synthesis will evaluate the effects of theory-based interventions, highlighting the anticipated contributions of theoretical frameworks to intervention outcomes. Expected impacts The anticipated findings aim to inform future evidence-based guidelines for integration into primary care, supporting the development of accessible, scalable, and effective mental health solutions globally.